Persepsi Pemuda Gereja Protestan Indonesia Banggai Kepulauan Namaasi Meselesek Tentang Jodoh Seiman - Sinaepon, Marce; Sopang, Oskar; Frans, Edison (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2024)
This study aims to describe the perceptions of the youth of Namaasi Meselesek Congregation regarding having a partner of the same faith. The main issue investigated is the beliefs and views of church youth about the importance of having a partner of the same faith in a pluralistic society. The subjects of the study are the youth of the Protestant Christian Church in Indonesia (GPIBK) Namaasi Meselesek Congregation. The research method used is descriptive quantitative with a survey approach. The entire population of church youth was used as the research sample, with data collected through a Likert scale-based questionnaire. The data analysis technique used is descriptive analysis with the help of SPSS. The study's findings indicate: first, respondents have a strong belief that a partner must share the same faith, rejecting various reasons such as happiness, love, age pressure, economic conditions, and pregnancy situations to choose a partner of a different faith. Second, there is awareness of the difficulty in finding a partner of the same faith in a predominantly non-Christian society. Third, despite holding firmly to the principle of having a partner of the same faith, respondents reject a partner of the same faith if they have bad behavior. This reflects their commitment to Christian principles and awareness of the social challenges present. This study provides both theoretical and practical insights for church communities and studies on the influence of religion in choosing a life partner.